Cannabinoid receptors are differentially regulated in the pancreatic islets during the early development of metabolic syndrome. Issue 6 (1st November 2020) - Barajas-Martínez, Antonio; Bermeo, Karina; de la Cruz, Lizbeth; Martínez-Vargas, Marina; Martínez-Tapia, Ricardo Jesús; García, David Erasmo; Navarro, Luz
ABSTRACT: The endocannabinoid system is found in tissues that regulate the glycemia, including adipose tissue, muscle, and pancreatic islets. Diet-induced metabolic syndrome changes the expression of the CB receptors in muscle, adipose tissue, and liver. However, it is poorly understood whether metabolic syndrome (MetS) affects the expression of CB receptors in pancreatic β cells. We analyzed the expression of CB receptors in pancreatic β cells under chronic high-sucrose diet (HSD)-induced MetS. Wistar rats fed an HSD as a model of MetS were used to investigate changes in cannabinoid receptors. After 8 weeks of treatment, we evaluated the appearance of the following MetS biomarkers: glucose intolerance, hyperinsulinemia, insulin resistance, hypertriglyceridemia, and an increase in visceral adiposity. To determine the presence of CB1 and CB2 receptors in pancreatic β cells, immunofluorescence of primary cell cultures and pancreatic sections was performed. For whole-islet quantification of membrane-bound CB1 and CB2 receptors, western-blotting following differential centrifugation was conducted. Our results revealed that an HSD treatment closely mimics the alterations seen in MetS. We observed that in primary cell culture, CB1 and CB2 receptors were expressed at a higher level in pancreatic β cells compared with non-β cells. MetS resulted in a reduction of CB1 in the islet, whereas abundant CB2 was observed after the treatment. CB1 and CB2 receptors are differentially expressed in pancreatic β cells during MetS development.